The Political Economy of Pension Reform: Public Opinion in Latin America and the Caribbean - Fabiana V.P. Machado; Giselle Vesga (Inter-American Development Bank (IDB), 2015)
Countries around the world are facing important challenges to the sustainability of their pension systems. Changing policies, especially those of large scope and financial magnitude, is a political challenge. It takes a combination of willingness, capacity and enough political support to change the status quo and avoid costly subsequent reversals. Taking advantage of several waves of public opinion data in Latin America and the Caribbean, this paper aims to identify and analyze individual-level factors that are relevant to gauging political support for pension reform.
hdl:11319/7258
Keywords: D72; H55; P16; 330; Political economy of reform; Pension reform; Public opinion